Pengaruh Motivasi dan Minat Belajar terhadap Hasil Belajar Siswa pada Mata Pelajaran Dasar-dasar Kejuruan Desain Komunikasi Visual di SMK Negeri 1 Batipuh - Pratama, Muhammad Iqbal; Marta, Rizkayeni (TSAQOFAH, 2025)
This study is grounded in the recognition of the importance of internal factors such as learning motivation and interest in supporting students' academic achievement, particularly in the subject of Basic Vocational Competencies in Visual Communication Design at vocational high schools (SMK). The purpose of this study is to examine the influence of learning motivation and interest on the academic performance of Grade X students in the Visual Communication Design program at SMK Negeri 1 Batipuh. A quantitative approach with a correlational method was employed. The sample consisted of 62 students selected from the entire population of Grade X students. Data were collected using a closed-ended questionnaire previously tested for validity and reliability, and documentation of Mid-Semester Examination (UTS) scores. Data analysis was conducted using IBM SPSS Statistics 2024. The results indicate that students’ motivation and learning interest are in the good category and have a strong, significant relationship with academic achievement, both individually and collectively, with a multiple correlation value of 0.867. The study concludes that learning motivation and interest exert a positive and significant influence on students’ academic performance. These findings imply the necessity of instructional strategies that foster student motivation and interest as a means to enhance academic achievement in vocational education.